2010
DOI: 10.1038/onc.2010.76
|View full text |Cite
|
Sign up to set email alerts
|

Potential utility of HOP homeobox gene promoter methylation as a marker of tumor aggressiveness in gastric cancer

Abstract: HOP homeobox (HOPX) is an unusual homeobox gene encoding three spliced transcript variants, among which the only HOPX-b promoter harbors CpG islands. The characteristics of its promoter methylation was analyzed using bisulfite sequencing and quantitative-methylationspecific polymerase chain reaction (Q-MSP), and the effects of HOPX expression were also examined. HOPX-b expression was silenced in all gastric cancer cell lines tested; its expression could be restored by treatment with demethylating agent. On Q-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(102 citation statements)
references
References 38 publications
(47 reference statements)
10
89
0
3
Order By: Relevance
“…One of this genes is HOP which encodes the Hsp70-Hsp90 Organizing Protein (gene ID 84525), and abnormal methylation of this gene has been recently associated with different types of cancer. [25][26][27] The differential methylation of HOP in the ART group was confirmed using a pyrosequencing assay (Fig. 5).…”
Section: Does the Association Of Art With Global Methylation Vary Witmentioning
confidence: 76%
“…One of this genes is HOP which encodes the Hsp70-Hsp90 Organizing Protein (gene ID 84525), and abnormal methylation of this gene has been recently associated with different types of cancer. [25][26][27] The differential methylation of HOP in the ART group was confirmed using a pyrosequencing assay (Fig. 5).…”
Section: Does the Association Of Art With Global Methylation Vary Witmentioning
confidence: 76%
“…Previous work documented the decreased HOPX expression in several types of human cancer. Explicitly, HOPX was suggested as tumor suppressor in esophageal and gastric cancer (17,23). These studies, however, did not study the role of HOPX in tumor dissemination and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…1A) and found a significant decrease in the HOPX mRNA level in PR9692-E9 cells. Transcriptional suppression of HOPX expression has repeatedly been correlated with promoter hypermethylation (15,16,23,24). To test the epigenetic character of HOPX suppression, we examined the HOPX methylation status in PR9692 and PR9692-E9 cells by bisulfite sequencing.…”
Section: Decreased Hopx Expression In the Nonmetastatic Pr9692-e9 Cellsmentioning
confidence: 99%
“…1A. The Reprimo promoter harbors CpG islands encompassing the transcription start site, and we previously reported that Reprimo harbored its promoter methylation in 75% (6/8) of gastric cancer cell lines, 80% (8/10) of primary human gastric cancer tissues, and 10% (1/10) of corresponding normal tissues in the preliminary dataset of 10 matched pairs by bisulfite sequencing analysis (15). Q-MSP can achieve a much more objective and specific assessment of a small amount of genomic DNA through PCR amplification using methylation-specific primers and fluorescent probes (22).…”
Section: Cancer-specific Reprimo Promoter Methylation In Gastric Cancermentioning
confidence: 95%
“…Furthermore, the regulation of Reprimo expression is independent of p53 status in neuronal cells treated with copper, with neuronal damage being associated with Wilson disease (14). In gastric cancer, Reprimo promoter methylation is a frequent event as we and others have previously reported (11,13,15). The relationship between Reprimo and gastric cancer, however, has never been examined from a mechanistic and functional point of view.…”
Section: Introductionmentioning
confidence: 98%